Contemporary Dynamics in Islamic Banking Transactions - Arfaizar, Januariansyah; Gustanto, Edo Segara; Fikri, Muhammad (TATHO: International Journal of Islamic Thought and Sciences, 2024)
Transactions in Islamic banking are currently the choice of the community because its products are based on Sharia with elements of maslahat. Now is the momentum for Islamic banking to fix the problems in its transactions to gain public trust and develop the potential possessed by Islamic banking. This research aims to examine transactions in Islamic banking and their problems using qualitative research methods and types of literature study research. This research explains that transactions in Islamic banking have five rules: benefit, fairness, pleasure, honesty, and piety. This research also found that in Islamic banking transactions, there are several internal problems in the form of inadequate human resources, Islamic economic regulations, unsupportive facilities, and infrastructure. Externally, not all people know about Islamic banking and its products.